Materials for Polymer Electrolyte Fuel Cells - Lorenz Gubler; Bashyam Rajesh; Alexander Wokaun; Günther G. Scherer; Beat Steiger; Andreas Reiner; Denis Kramer; Faegheh Hajbolouri; Selmiye Alkan Gürsel; Nina Beck; K. Ravindranathan Thampi (CHIMIA, 2004)
The commercial success of the polymer electrolyte fuel cell (PEFC) will to a large extent be determined by the nature, properties, functionality, and cost of the electrochemical sub-components used in the membrane electrode assembly (MEA). Materials research activities in Switzerland for the PEFC are being pursued at the Paul Scherrer Institut (Villigen AG) and the Swiss Federal Institute of Technology in Lausanne with different objectives. The radiation grafted proton exchange membrane developed at the Paul Scherrer Institut (PSI) has been brought to a near-product-like quality level with encouraging performance close to state-of-the-art materials and a life-time of several thousand hours. Furthermore, the membrane shows low methanol crossover in the direct methanol fuel cell. In addition, polyarylene block copolymer membranes have been investigated as an option for fluorine-free membranes. The electrocatalysis of Pt in acidic solution and in contact with a solid electrolyte, the development of new methanol oxidation and oxygen reduction catalysts, and co-sputtering of Pt and carbon as an alternative method for catalyst preparation are areas of fundamental research. More applied research is performed in the characterization of commercial electrodes in single cells, using standard as well as advanced diagnostic tools developed in-house. This article gives an overview over the research and development projects in Switzerland related to materials and components for the PEFC.